The Adomian decomposition method for the approximate solution of homogeneous differential equations with dual variable and dual coefficients - Asil, V; Bulut, H; Evans, DJ (Taylor & Francis Ltd, 2005)
In this study, the decomposition method of Adomian has been applied for the approximate solution of homogeneous differential equations with dual variable and dual coefficients.
Keywords: nonlinear hyperbolic equation; the decomposition method; dual numbers; dual vectors; dual function; exponential map; laplace transformations